Longe da vista, perto da imaginação: análise de audioguias em museus portugueses - Martins, Cláudia (2015)
The current research project is set within the scope of Audiovisual Translation (AVT), with a descriptive, multimodal and multidisciplinary approach. More particularly, it aims at approaching the AVT accessibility solutions, by means of audio description. Audio description as a means to describe all the dimensions of life has been applied to numerous cultural and leisure contexts, namely to the cinema, theatre, music and opera, as well as museums and galleries, and has reached its height in the 1980s in the US and the UK. In highly visual places, such as museums, audio description is of the utmost importance for the access of blind and visually-impaired visitors, but it can not be the only means available. Mediation must be conducted according to different communication forms, such as information materials (labels for the objects under exhibition, museum text on walls text, room texts, leaflets and brochures) in large print or in Braille, guided visits, audio guides or descriptive guides, touch materials and hands-on experiences, included or not in the activities of the educational services. Museum accessibility for visually-impaired audiences is more complex than what might be expected and demands a holistic approach that encompasses the abovementioned aspects. Therefore, based on the theoretical principles retrieved from Disability Studies, Audiovisual Translation Studies and Museum Studies, we developed the empirical study of this thesis, which comprehends a two-fold approach: on the one hand, a case study (of phenomenological research) that focuses on listing the Portuguese institutions that offer descriptive guides, describing the visits undertaken to a representative sample of these institutions and their subsequent characterisation, and, on the other, a corpus study that analyses qualitatively a sample of 35 audio commentaries. From this empirical component, we intend to describe the accessibility practices in Portugal in terms of institutional, technical and macrostructural criteria, as well as the descriptive guides from these institutions, according to their conformity to a set of microstructural criteria.